2022
DOI: 10.7759/cureus.29620
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Abscopal Effect in the Era of Immunotherapy

Abstract: The abscopal effect is a systemic immune response mediated by the effects of radiation on the immune system. This effect has been observed in a number of cancer types in addition to lung cancer, including but not limited to renal cell carcinoma, hepatocellular carcinoma, lymphoma, and melanoma. The combination of radiation therapy and immune checkpoint inhibition (ICI) acts at several stages of the antitumor response, suggesting a mechanism of synergy between the two modalities. This review focuses on recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Enhancement of immune response to tumor cells by RT has been demonstrated in experimental studies, both in relation to CAR‐T‐cell therapy and in relation to checkpoint inhibitors 27,38,39 . A particular interest has centered on the abscopal effect of RT, that is, the disappearance or reduction of neoplastic lesions located outside the irradiated volume 40–45 . However, despite the reports, this effect is seen rarely and unpredictably, and it has still not been possible to exploit this phenomenon clinically.…”
Section: Primingmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of immune response to tumor cells by RT has been demonstrated in experimental studies, both in relation to CAR‐T‐cell therapy and in relation to checkpoint inhibitors 27,38,39 . A particular interest has centered on the abscopal effect of RT, that is, the disappearance or reduction of neoplastic lesions located outside the irradiated volume 40–45 . However, despite the reports, this effect is seen rarely and unpredictably, and it has still not been possible to exploit this phenomenon clinically.…”
Section: Primingmentioning
confidence: 99%
“…27,38,39 A particular interest has centered on the abscopal effect of RT, that is, the disappearance or reduction of neoplastic lesions located outside the irradiated volume. [40][41][42][43][44][45] However, despite the reports, this effect is seen rarely and unpredictably, and it has still not been possible to exploit this phenomenon clinically. Part of the reason may be that RT can exert both positive and negative effects on the immune system.…”
mentioning
confidence: 99%
“…[35][36][37] Although most data for abscopal effect comes from non-small-cell lung cancer (NSCLC), it has been observed in other cancers. 38 Verma et al analyzed the safety of combined immunotherapy and TRT (iRT) in patients from three phase I/II trials and found combined iRT to be safe in the short term (median follow-up was 6.9 months (range, 0.5-30.9 months). 39 The safety of combining ICI and RT was tested in another phase I trial, which enrolled patients with ES-SCLC treated with induction CHT followed by concurrent pembrolizumab and TRT (45 Gy in 15 fractions, with simultaneous integrated boost to the gross tumor allowed to 52.5 Gy).…”
Section: Thoracic Radiotherapy In Es-sclcmentioning
confidence: 99%
“…Critically, these improvements result in significant changes in serum cytokine signalling that is transmitted across the body [14]. This may be mediating the abscopal effect [15]. This effect is established in cancer treatment where specific irradiation of a primary tumour can result in shrinkage of distally located secondary tumours.…”
Section: Introductionmentioning
confidence: 99%